Gene cloning, characterization and thermodynamic analysis of a novel multidomain hyperthermophilic GH family 3 β-glucosidase (TnBglB) from Thermotoga naphthophila RKU-10T. (March 2018) - Akram, Fatima; Haq, Ikram ul; Mukhtar, Hamid
Graphical abstract: Highlights: A novel hyperthermophilic β-glucosidase was cloned from Thermotoga naphthophila . Highly active TnBgl B is a three-domain protein belonging to GH family 3. Purified TnBgl B showed great stability at 85 °C for 540 min, mainly at pH 6.0–7.5. Recombinant TnBgl B activity was increased to 175% with the addition of Ca 2+ . Abstract: The gene of a multidomain glycoside hydrolase family 3 β-glucosidase ( TnBgl B) was cloned from a hyperthermophilic Thermotoga naphthophila RKU-10 T and overexpressed in Escherichia coli BL21 CodonPlus (DE3)-RIPL. Extracellular TnBgl B was purified to homogeneity using heat precipitation, followed by anion-exchange and hydrophobic interaction chromatography, with a molecular weight of 81 kDa on SDS-PAGE. TnBgl B exhibited great affinity towards p -nitrophenyl and cellobiose substrates. The enzyme was optimally active at 85 °C and pH 5.0, and showed great thermostability over a broad range of temperature (60–85 °C) mainly at pH 6.0–7.5 for 540 min. TnBgl B activity was stimulated with Ca 2+ addition. The K i value was 150 mM and 200 mM for glucose and xylose inhibition, respectively. K m, V max, k cat and k cat Km − 1 values were 0.45 mM, 153 mmolmg −1 min −1, 1214285 s −1 and 2698413 mM −1 s −1, respectively using p NPG as substrate. Thermodynamic parameters as Δ H *, Δ G * and Δ S * for p NPG hydrolysis at 85 °C were 24.09 kJ mol −1, 46.55 kJ mol −1 and −62.74 Jmol −1 K −1, respectively. TnBgl B displayed a half-life ( t1/2 ) of 4.44 min at 94 °C with denaturation parameters including Δ H* D, Δ G *D and Δ S* D were 283.78 kJ mol −1, 108.69 kJ mol −1 and 0.477 kJ mol −1 K −1, respectively. This hyperthermostable multimodular β-glucosidase exhibited noteworthy properties, which make it a favorable candidate for various industrial applications.